Dialogic interaction with diversified audiences in Twitter for Research Dissemination Purposes - Pascual, Daniel; Mur-Dueñas, Pilar (Círculo de Lingüística Aplicada a la Comunicación, 2022)
International research groups are expected to ensure global dissemination and visibility of their knowledge production, for which Twitter is effectively employed to reach diversified audiences. This paper analyses the dialogic dimension of tweets published in accounts of Horizon2020 research projects, where group’s productivity and work are promoted, and multiple readers addressed. Our study focuses on the use, in these Twitter accounts, of interactional pragmatic strategies, their verbal realisation through engagement markers, as well as on medium affordances and non-verbal markers. A sample of 1.454 tweets from 10 accounts of the EUROPROtweets corpus were coded and analysed through NVivo. The data-driven pragmatic analysis triggered the identification of 8 interactional strategies. We then quantitatively analysed the use of engagement makers and qualitatively studied the characteristic non-verbal markers with a dialogic function within each of these. Our findings will help understand the complexities of current digital academic professional practices, especially as regards the dynamics of dialogic interaction in social media.